Relation Between Creativity and Economy in the Creative Economy (A Case Study on Acapella Mataraman Musical Parody Community) - Firmansah Firmansah (IJCAS (International Journal of Creative and Arts Studies), 2015)
The aim of this study is to determine and to explain the relationship between creativity and economics. This phenomenon can be seen through the performing arts community in the era of government policy on creative economy which established in 2007. As the qualitative study, this study used case study approaches to Acapella Mataraman community .This study also used the economic concept art by Ruth Towse. The research finding of this study is the creative economy logic of the government can create important factors of increasing the level of creativity. So that Pardiman as the intellectual and major figure in Acapella Mataraman community is able to classify his creativity on consumer’s price demand. In addition, the non-profit aspect also can be applied by Pardiman as the Acapella Mataraman community promotion in the performing arts market.